Mesenchymal stem cells from human umbilical cord decrease inflammation and increase vascularization of induced apical periodontitis model in diabetes mellitus rats - Eric Priyo Prasetyo; Devi Eka Juniarti; Mefina Kuntjoro; Nike Hendrijantini; Aditya Arinta Putra; Wanda Oktaria; Zellita Fresticia Rosmaida Devi Hutapea; Evelyn Tjendronegoro (University of São Paulo, 2024)
Abstract Objectives: to evaluate inflammation and vascularization in a model of apical periodontitis in diabetic Wistar rats through histopathological examination of blood vessels and immunohistochemical examination of interleukin 1b (IL-1b) and tumor necrosis factor-a (TNF-a). Methodology: Diabetes was induced in 20 Wistar rats using multiple low-dose injections of streptozotocin (STZ) until blood glucose levels stabilized above 300 mg/dL, confirmed by glucometer. Under anesthesia, apical periodontitis was induced in the right mandibular first molars. After preparing the access cavity and extirpating pulp and canal, the teeth were left open. Apical periodontitis was projected seven days afterwards and the Wistar rats were assigned in random into four groups, each group consisting of five rats. The first group (C14) was euthanized 14 days post-induction, while the second group (C28) was euthanized 28 days later, serving as controls. The third group (T14) received mesenchymal stem cells from human umbilical cords and was euthanized after 14 days, while the fourth group (T28) received mesenchymal stem cells from human umbilical cord and was euthanized after 28 days. The number of blood vessels and the expressions of IL-1b and TNF-a were analyzed. Data were evaluated with ANOVA and by Tukey's HSD test, with significance at p<0.05. Results: Both control and treatment groups showed a significant increase in vascularization in the apical periodontal area of apical periodontitis in the control and treatment groups at 14 and 28 days (p<0.05). A significant reduction of IL-1b and TNF-a levels was found in the mesenchymal stem cells treatment groups when compared to control groups (p<0.05). Conclusion: Our findings support the use of mesenchymal stem cells from human umbilical cords to decrease inflammation and increase vascularization in an induced apical periodontitis model in diabetes mellitus Wistar rats.